Dermatoscopic features of pigmented intraepidermal carcinoma on the head and neck. (25th August 2020) - Inskip, Michael; Cameron, Alan; Akay, Bengu Nisa; Gorji, Mahdieh; Clark, Simon P; Rosendahl, Nikita; Coetzer‐Botha, Martelle; Kittler, Harald; Rosendahl, Cliff
Summary: Background and Objective: Pigmented intraepidermal carcinoma is characterized by dermatoscopic dots and structureless areas, including dots in linear arrangement and by coiled vessels. There are no studies describing the dermatoscopic features of pigmented intraepidermal carcinoma on the head and neck. We aim to characterize the clinical and dermatoscopic appearance of this entity. Patients and Methods: We retrospectively analyzed 79 cases of pigmented intraepidermal carcinoma on the head and neck. Results: Pigmented intraepidermal carcinoma on the head and neck was characterized dermatoscopically by multiple colors (98.7 %, n = 78), pigmented circles (48.1 %, n = 38), white circles (17.7 %, n = 14), angulated lines (41.8 %, n = 33) and structureless areas (86.1 %, n = 68). Dots in linear arrangement were present in 13.9 % (n = 11). Coiled vessels were present in 7.6 % (n = 6), the dominant vessel type being prominent serpentine vessels (29.2 %, n = 23), thicker and/or redder in color than surrounding vessels, most being in the angular arrangement of the dermal plexus (24.1 %, n = 19). Conclusions: Pigmented intraepidermal carcinoma on the head and neck differs from current published descriptions of pigmented intraepidermal carcinoma, reaching statistical significance with a lower incidence of coiled vessels and a higher incidence of pigmented circles, with evident similarities to pigmented actinic keratosis at that location.